ENGLISH AS A FOREIGN LANGUAGE TEACHERS' BELIEFS ABOUT GRAMMAR TEACHING IN CLASSROOM - Ananda Fitriyani; Silih Warni; Nita Kaniadewi (ELLTER Journal, 2020)
This study investigated English as a Foreign Language teachers’ beliefs toward grammar teaching in the classroom. This research paper aimed to explore EFL teachers’ belief about grammar teaching and the factors influencing teachers in shaping their beliefs on grammar teaching. A qualitative study using a semi-structured interview with eight English as foreign language teachers of secondary schools in East Jakarta has been conducted. The result revealed that most teachers believed that grammar was essential. Explicit grammar teaching was also believed to be more effective to be implemented in teaching grammar, yet teachers still used both explicit and implicit instructions. Nonetheless, some teachers believed that implicit instruction that was suggested in the 2013 Curriculum was less effective due to the limited time of English learning in classroom practice. The factors shaping the teachers’ beliefs involved the student factor and the teacher factors which included teachers’ prior education and personal experiences. This research was expected to improve the teaching of grammar practices and suggest an effective approach to be implemented in teaching grammar in EFL context for teachers in classroom.